The relationship between the axial length of the eye ball and the retinal vein occlusion - Kouser, Firdose; Kai, Sanjay; Gupta, Divyanshi; Raina, Bhavani; Pushp, Shahaan (International Journal of Research in Medical Sciences, 2023)
Background: Retinal vein occlusion is one of the most common form of retinal vascular diseases. There’s a need for better understanding of various predisposing factors and pathophysiology of retinal vascular occlusions in order to improve the treatment modalities and have a better visual outcome including the relationship between axial length and retinal vascular occlusions. Methods: The study was conducted on 60 patients attending the eye OPDs of upgraded department of ophthalmology of government medical college, Jammu during a period of six months from April 2022 to September 2022. 30 patients were clinically diagnosed cases of retinal vein occlusion whereas 30 patients were their age and sex matched controls. The axial length of both eyes of all the patients were measured using A scan Biometry. The data was then analysed by student t test and chi square test. Results: It was found that the axial length of the affected eye was significantly shorter than the unaffected eye and the axial length of the unaffected eye was also significantly shorter than the control eye. Conclusions: It was concluded that the axial lengths in the patients having retinal vein occlusion were significantly shorter than the controls. The significant difference in the axial lengths can be a risk factor in the development of retinal vein occlusion.